(untitled) (Herald of the National Children’s Medical Center, 2025)
CAR-T cell therapy has emerged as a promising treatment for relapsed/refractory B-cell non-Hodgkin lymphoma (R/R B-NHL), especially in patients with limited therapeutic options. We report the case of a 60-year-old male with primary chemotherapy-refractory diffuse large B-cell lymphoma (DLBCL) and comorbidities including diabetes, hypertension, and stable coronary artery disease, treated with anti-CD19 CAR-T cell therapy (NEXCAR19) at MIOT International, Chennai. Following disease progression after seven cycles of R-CHOP chemotherapy and consolidation radiotherapy, lymphocyte apheresis was performed, yielding sufficient starting material for CAR-T cell production. The patient received fludarabine–cyclophosphamide conditioning followed by infusion of 100 mL of NEXCAR19 CAR-T cells, which was well tolerated without cytokine release syndrome or immune effector cell-associated neurotoxicity syndrome. PET-CT at day +29 demonstrated a marked metabolic response (Deauville score 4). Low-dose nivolumab maintenance therapy and IMRT- based consolidation radiotherapy to residual abdominal nodes were introduced to enhance remission durability and CAR-T sensitization. This case illustrates the feasibility, safety, and promising early efficacy of anti-CD19 CAR-T therapy in chemo-refractory DLBCL and highlights the potential benefit of integrating immunotherapy with targeted radiotherapy. Long-term follow-up will determine relapse risk and sustained response.